PRIORITY NEEDS FOR DEVELOPING TEACHER’S OUTDOOR LEADERSHIP OF WAT HUAY CHORKHAE WITTAYAKOM SCHOOL - Suwannathai , Aukarapol; Jariyarangsiroge, Apiradee (Journal of Educational Review Faculty of Education in MCU, 2025)
This research is a descriptive study aimed at examining the current conditions, desired conditions, and development needs for outdoor activity leadership among teachers at Wat Huai Chorkhae Wittayakom School. The population consisted of 112 teachers from Wat Huai Chorkhae Wittayakom School. The research instrument was a rating scale questionnaire with content validity of 1.00 and reliability of 0.949. Statistical analyses employed included frequency, percentage, arithmetic mean standard deviation, Priority Needs Index (PNImodified), and content analysis. The research findings revealed that the current state of outdoor activity leadership development among teachers at Wat Huai Chorkhae Wittayakom School was at a moderate level overall. The desired state of outdoor activity leadership development among teachers at Wat Huai Chorkhae Wittayakom School was at the highest level overall. Regarding the development needs for outdoor activity leadership among teachers at Wat Huai Chorkhae Wittayakom School, the findings showed that the skill with the highest Priority Needs Index was safety skills (PNImodified = 0.81), followed by resource management skills (PNImodified = 0.79), outdoor technical skills (PNImodified = 0.78), problem-solving skills (PNImodified = 0.76), and communication skills (PNImodified = 0.70), respectively.